Pengaruh Faktor Determinan Sektor Perkebunan Kelapa Sawit terhadap Pertumbuhan Sektor Pertanian di Sumatera Utara: Suatu Analisis - Muhammad Fitri Rahmadana (Outline Publisher, 2022)
This research aims to investigate the impact of several factors, specifically, the area of oil palm plantations, oil palm production, and the number of workers in the agricultural sector on the agricultural sector's Gross Regional Domestic Product (GRDP) in North Sumatra Province. The study employs secondary data obtained from BPS North Sumatra Province, including PDRB variables in the agricultural sector, the area of oil palm plantations, palm oil production, and the number of workers in the agricultural sector in five districts, namely Asahan, Langkat, Labuhanbatu Utara, Labuhanbatu Selatan, and Labuhan Batu districts. The time series data span from 2008 to 2017. The Ordinary Least Square (OLS) method with a panel data regression estimation model using Eviews 10 was applied to analyze the data. The findings indicate that the collective effect of the independent variables, namely land area, production, and the total workforce of the agricultural sector, has a significant impact on the agricultural sector's GRDP. Furthermore, the results reveal that the land area and palm oil production variables have a positive and significant impact on the agricultural sector's GRDP in North Sumatra Province. In contrast, the labor force in the agricultural sector has a negative effect on the agricultural sector's GRDP in North Sumatra Province.This research aims to investigate the impact of several factors, specifically, the area of oil palm plantations, oil palm production, and the number of workers in the agricultural sector on the agricultural sector's Gross Regional Domestic Product (GRDP) in North Sumatra Province. The study employs secondary data obtained from BPS North Sumatra Province, including PDRB variables in the agricultural sector, the area of oil palm plantations, palm oil production, and the number of workers in the agricultural sector in five districts, namely Asahan, Langkat, Labuhanbatu Utara, Labuhanbatu Selatan, and Labuhan Batu districts. The time series data span from 2008 to 2017. The Ordinary Least Square (OLS) method with a panel data regression estimation model using Eviews 10 was applied to analyze the data. The findings indicate that the collective effect of the independent variables, namely land area, production, and the total workforce of the agricultural sector, has a significant impact on the agricultural sector's GRDP. Furthermore, the results reveal that the land area and palm oil production variables have a positive and significant impact on the agricultural sector's GRDP in North Sumatra Province. In contrast, the labor force in the agricultural sector has a negative effect on the agricultural sector's GRDP in North Sumatra Province.